Ação da dopamina na secreção do hormônio do crescimento em novilhas pré-púberes da raça Nelore - Santana Batista, Emiliana Oliveira; Cardoso, Daniel; Nogueira, Guilherme de Paula [UNESP] (Univ Estadual Londrina, 2014)
The aim of this study was to evaluate the response of dopamine in the growth hormone secretion (GH) during Nellore heifer's sexual maturation. The animals were randomly assigned into two experimental groups: Sulpiride group (dopamine D-2 antagonist, 0.59 mg/kg, S. C.) and control group (saline solution S. C.) at 8, 12 and 16 months of age. Blood samples were collected every 15 min for 10h after drug injection. Growth hormone was quantified by RIA, sensitivity (0.25 ng/mL) and intra and inter-assay variation coefficients were 15% and 17%, respectively. GH concentration was higher in sulpiride group than control group at 8 mo (10.1 +/- 0.38 ng/mL vs 4.3 +/- 0.34 ng/mL; P < 0.05) and 12 mo of age (9.46 +/- 0.35 vs 3.74 +/- 0.19 ng/mL; P < 0.05). In sulpiride group GH average concentration was greater at 8 and 12 mo compared to 16 mo of age (10.10 +/- 0.38 ng/mL and 9.46 +/- 0.35 ng/mL vs 4.87 +/- 0.35 ng/mL; P < 0.05) respectively. There was no difference between groups (P > 0.05) in total GH secretion area, total peak area and maximum peak amplitude. These results suggested an inhibitory dopamine effect on GH secretion in pre-pubertal Nellore heifers that decreases according to age.
Dopamine action in prepubertal Nelore heifers growth hormone secretion
Keywords: Bos indicus; hypothalamus; puberty; sulpiride